Resolving Tumor Heterogeneity: Genes Involved in Chordoma Cell Development Identified by Low-Template Analysis of Morphologically Distinct Cells - El-Heliebi, Amin (Public Library of Science, 2014)
The classical sacrococcygeal chordoma tumor presents with a typical morphology of lobulated myxoid tumor tissue with cords, strands and nests of tumor cells. The population of cells consists of small non-vacuolated cells, intermediate cells with a wide range of vacuolization and large heavily vacuolated (physaliferous) cells. To date analysis was only performed on bulk tumor mass because of its rare incidence, lack of suited model systems and technical limitations thereby neglecting its heterogeneous composition. We intended to clarify whether the observed cell types are derived from genetically distinct clones or represent different phenotypes. Furthermore, we aimed at elucidating the differences between small non-vacuolated and large physaliferous cells on the genomic and transcriptomic level. Phenotype-specific analyses of small non-vacuolated and large physaliferous cells in two independent chordoma cell lines yielded four candidate genes involved in chordoma cell development. UCHL3, coding for an ubiquitin hydrolase, was found to be over-expressed in the large physaliferous cell phenotype of MUG-Chor1 (18.7-fold) and U-CH1 (3.7-fold) cells. The mannosyltransferase ALG11 (695-fold) and the phosphatase subunit PPP2CB (18.6-fold) were found to be up-regulated in large physaliferous MUG-Chor1 cells showing a similar trend in U-CH1 cells. TMEM144, an orphan 10-transmembrane family receptor, yielded contradictory data as cDNA microarray analysis showed up- but RT-qPCR data down-regulation in large physaliferous MUG-Chor1 cells. Isolation of few but morphologically identical cells allowed us to overcome the limitations of bulk analysis in chordoma research. We identified the different chordoma cell phenotypes to be part of a developmental process and discovered new genes linked to chordoma cell development representing potential targets for further research in chordoma tumor biology.